Insertion site of central venous catheter among hospitalized adult patients: A systematic review and network meta-analysis - Sakuraya, Masaaki; Okano, Hiromu; Yoshihiro, Shodai; Niida, Shoko; Kimura, Keina (Frontiers in Medicine, 2022)
Introduction Central venous catheterization is a commonly performed procedure, accounting for approximately 8% of hospitalized patients. Based on the current literatures, the most acceptable site for central venous catheterization is inconclusive, considering various complications in hospitalized patients. Herein, we conducted a network meta-analysis to assess the clinically important complications among internal jugular, subclavian, femoral, and peripheral insertion. Materials and methods The Cochrane Central Register of Controlled Trials, MEDLINE, Web of Science, Ichushi databases, Clinicaltrials.gov, and International Clinical Trials Registry Platform were searched. Studies including adults aged ≥ 18 years and randomized control trials that compared two different insertion sites (internal jugular, subclavian, femoral, and peripheral vein) were selected. The primary outcomes were clinically important infectious, thrombotic, and mechanical complications. Results Among the 5,819 records initially identified, 13 trials (6,201 patients) were included for a network meta-analysis. For clinically important infectious complication, subclavian insertion decreased the complication risk, compared with internal jugular [risk ratio (RR), 0.30; 95% confidence interval (CI), 0.11–0.81; moderate certainty], and femoral insertion increased than subclavian insertion (RR 2.56; 95% CI, 1.02–6.44; moderate certainty). Peripheral insertion was also significantly associated with a lower risk compared with internal jugular (RR 0.06; 95% CI, 0.01–0.32; low certainty); subclavian (RR 0.21; 95% CI, 0.05–0.77; moderate certainty); and femoral insertion (RR 0.08; 95% CI, 0.02–0.40; low certainty). For clinically important thrombotic complication, we did not find significant differences between insertion sites. For clinically important mechanical complication, femoral insertion decreased the complication risk, compared with internal jugular (RR 0.42; 95% CI, 0.21–0.82; moderate certainty) and subclavian insertion (RR 0.33; 95% CI, 0.16–0.66; moderate certainty). Peripheral insertion was also associated with the lower complication risk compared with internal jugular (RR 0.39; 95% CI, 0.18–0.85; low certainty) and subclavian insertion (RR 0.31; 95% CI, 0.13–0.75; moderate certainty). Conclusion The insertion site of the central venous catheter, which is most likely to cause the fewest complications, should be selected. Our findings can provide the rationale for deciding the insertion site for a central venous catheter. Systematic review registration [www.protocols.io], identifier [61375].